DESIGN AND DEVELOPMENT OF AN OPTICAL GONIOMETER - Mohamad Azalan, Nur Haaziq (2018)
Optical Goniometer is a tool to measure the wettability of liquid by measuring the contact angle of the liquid droplet. Basically, wettability is the phenomenon of liquid spreading on a solid surface in which this phenomenon plays a crucial role in many applications. This project touches upon the design and development of a low cost and portable optical goniometer. The principle of this optical goniometer to optically measure the contact angle from the image of a liquid droplet captured by a camera. The design criteria are to have changeable solid materials and liquid phase. The optical goniometer can test 2 different types of measuring method which are sessile method and pendant method. Three conceptual designs for test cell have been created and from the three, one concept design was selected to be final design. Based on the selected design, one prototype has been successfully developed by using laser cutting machine, 3D printing method. Finally, the contact angle for water droplet in contact with steel surface has been successfully performed in the prototype and measured using the ImageJ software.